2006
DOI: 10.1016/j.visres.2006.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of foveal distractors on saccadic eye movements: A dead zone for the global effect

Abstract: Three experiments investigated the global effect with foveal distractors displayed in the same hemifield as more eccentric saccade targets. Distractors were x-letter strings of variable length and targets corresponded to the central letter of letter strings (e.g., 'xxxkxxx'). Results showed that only foveal distractors longer than four letters (about 1 degree) deviated the eyes in a center-of-gravity manner thus suggesting a dead zone for the global effect. Short distractors influenced the likelihood of small-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 60 publications
5
31
2
Order By: Relevance
“…Rejected trials represented 19.7% of the total number of trials across participants. This was in accordance with rejection rates obtained with a similar task and setup (see Vitu, Lancelin, Jean, & Farioli, 2006) and was mainly due to button press occurring before stimulus presentation or stimuli being displayed during a saccade and not during a fixation (8.6%) as well signal artifacts and blinks (5.8%). Other rejected trials were trials where no saccade was being made (1.4%), the saccade was anticipatory (3.7%), the saccade was in wrong direction (2%), or the initial fixation was not within the fixation window around the bars (0.8%).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Rejected trials represented 19.7% of the total number of trials across participants. This was in accordance with rejection rates obtained with a similar task and setup (see Vitu, Lancelin, Jean, & Farioli, 2006) and was mainly due to button press occurring before stimulus presentation or stimuli being displayed during a saccade and not during a fixation (8.6%) as well signal artifacts and blinks (5.8%). Other rejected trials were trials where no saccade was being made (1.4%), the saccade was anticipatory (3.7%), the saccade was in wrong direction (2%), or the initial fixation was not within the fixation window around the bars (0.8%).…”
Section: Resultssupporting
confidence: 89%
“…We previously reported that a foveal distractor stimulus fails to deviate the eyes from a more eccentric ipsilateral target when it extends within less than 1.258 from the center of the fovea, thus suggesting a foveal deadzone for the global effect (Vitu, 2008;Vitu et al, 2006). Here, we found a global effect with ipsilateral distractors in the central region, but this was greatly reduced as compared to the effect of more eccentric distractors.…”
Section: Accounting For Modulations Of the Global Effectsupporting
confidence: 40%
See 2 more Smart Citations
“…Trials were rejected when the stimuli were displayed during a saccade and not a fixation (4.8%), the averaged eye position before saccade onset (as measured offline) deviated from the fixation cross by more than ±0.5°and ±1°in the horizontal and the vertical directions respectively (10.4%), a blink occurred before or after the saccade (6.94%), the saccade was anticipatory (latency less than 80 ms; 9.66%) or it landed no further than 1°t o the right of fixation (10.39%), resulting in a total of 24.6% rejected trials on average across participants. Note that rejection percentages in the range of 20% are commonly observed in this type of task and setup (e.g., Vitu et al, 2006). After rejection, there remained 527 trials on average (range: 504-544) in each In all analyses, means were calculated for each participant, and these were then averaged across participants.…”
Section: Data Selection and Analysismentioning
confidence: 99%